Traumatic brain injury and automotive design: making motor vehicles safer. - Nirula R; Kaufman R; Tencer A (Journal of Trauma, 2003)
Background: Traumatic brain injury (TBI) remains a major public health problem in the United States. Identifying and modifying vehicle designs associated with TBI will have a significant impact on the frequency and severity of TBI in motor vehicle crashes (MVCs). Our objective, therefore, was to identify interior vehicle contact points associated with severe TBI (head Abbreviated Injury Scale score > 3) among drivers and determine the extent to which modifications of these contact points impact the likelihood of severe TBI.Methods: We analyzed drivers in MVCs from the 1993 to 2001 National Automotive Sampling System database. The odds of severe TBI with respect to various vehicle contact points were estimated using multivariate logistic regression. Using computer simulation software, the magnitude of driver head deceleration was modeled while manipulating vehicle design features. The potential impact of this design modification on the frequency and hospital charges of TBI cases was estimated.Results: There were 18,313 drivers involved who were victims of TBI, equating to a national sample size of 3,275,472 cases. The most frequent contact point associated with severe TBI was the roof rail (odds ratio, 2.0; 95% confidence interval, 1.2-3.3). Increasing roof rail padding thickness to 5.0 cm reduced the peak acceleration from 700 g to 218 g, which would potentially reduce the attributable number of severe TBI cases per year from 2,730 to 210, thereby reducing annual acute care charges from $136.5 million to $10.5 million.Conclusion: Contact with the roof rail significantly increases the likelihood of TBI in MVCs. Minor increases in padding at these points may reduce the frequency of severe TBI, which would have a substantial effect on health care costs.